Extraordinary Ordinariness: Realism Now and Then - Levine, Caroline (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2013)
Critics have often assumed that realism betrays its dedication to ordinary reality when it takes on lots of narrative and political excitement, but this article argues that realism works best when it combines humdrum routine with narrative shock. Levine claims that the nineteenth-century novel invented a paradoxical realist technique that has been adopted by contemporary serial television, which she calls “the shock of the banal.” Representing daily routines in ways that render them unfamiliar, funny, or strange, realist fictions strive to make ordinary experience feel extraordinary. This essay explores the formal, historical, and political implications of “the shock of the banal” in Adam Bede, Bleak House, and Uncle Tom’s Cabin, and their echoes in The Sopranos, Mad Men, and The Wire.